Financial access and productivity dynamics in Sub-Saharan Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
The purpose of this study is to investigate whether enhancing financial access influences productivity in Sub-Saharan Africa. The research focuses on 25 countries in the region with data for the period 1980-2014. The adopted empirical strategy is the Generalised Method of Moments. The credit channel of financial access is considered and proxied by private domestic credit while four main total factor productivity (TFP) dynamics are adopted for the study, namely: TFP, real TFP, welfare TFP and real welfare TFP. It is apparent from the findings that enhancing financial access positively affects welfare TFP whereas the effect is not significant on TFP, real TFP and welfare TFP. Policy implications are discussed. The study complements the extant literature by engaging hitherto unemployed dynamics of TFP in Sub-Saharan Africa.
Keywords: E23; F21; F30; O16; O55; 330; Economic Output; Financial Development; Sub-Saharan Africa